Student publication photo shoot - Spartan Daily:::Creator::::::::::::
Photo shoot of three students; two men and a woman. The white man shown on the left is wearing a poncho and flashing the peace sign with his fingers; in the center is a woman wearing a gas man; on the right is an African American man dressed in cultural African dress. This shoot was likely tied to the Survival Faire